Ржевское пекло - Зверев Сергей Иванович (Эксмо, 2021)
Экземпляры: ф.5 (20211209) / Инвентарный номер: 54457 / Цена: 334.00 / Сис.шифр: 84(2Рос=Рус)6 / Авт.знак: З-43 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)6